Implementation of Legislative Functions of The DPRD Asahan Regency for 2019-2024 Period from Perspective of Local Government Law in Indonesia - Dean Rendienta Sembiring; Janpatar Simamora; Januari Sitohang (Sultan Agung Notary Law Review, 2026)
This study aims to analyze the implementation of the legislative function of the Regional House of Representatives (DPRD) of Asahan Regency for the 2019–2024 period from the perspective of regional government law in Indonesia. This research employs a combined normative-empirical juridical method by examining relevant statutory regulations and field data obtained through interviews and document studies. The results indicate that the legislative function of the DPRD of Asahan Regency has been implemented in accordance with the stages of regional regulation formation, namely the planning and drafting stage, the discussion stage, and the ratification and promulgation stage. However, in practice, several obstacles remain, including the suboptimal absorption of public aspirations and insufficient research in the preparation of academic manuscripts for draft regional regulations. The variation in the number of draft regional regulations and enacted regional regulations during the 2019–2024 period reflects the dynamics and challenges in implementing the legislative function. From the perspective of regional government law, strengthening public participation, optimizing the role of the DPRD secretariat, and improving the quality of academic manuscripts are necessary to ensure that regional legal products align with good governance principles and community needs.